A gain boosting single stage cascode LNA for millimeter-wave applications - Harsoori, M.M. (IEEE Computer Society, 2018)
This paper presents the design of 60 GHz low noise amplifier (LNA) aimed at realizing IEEE 802.11ad standard using 0.13-Î¼m RF CMOS technology. Single stage cascode with source degeneration topology employing a gain boosting technique is adopted for better isolation and gain performance in millimeter-wave (mmW) frequency band. The simulation of the LNA yields the input reflection coefficient (S11) of -20.75 dB, forward transmission gain (S21) of 7.75 dB, and reverse isolation (Â£12) of 8.64 dB. The LNA design achieves a noise figure (NF) of 8.9 dB with minimum noise figure (NFmin) of 7.8 dB at 60 GHz. Thus, the design generates power dissipation of 15.17 mW for 1.2 V supply voltage. Â© 2017 IEEE.